2019
DOI: 10.1109/access.2019.2906668
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Adoption and Knowledge Management Sharing: An Empirical Investigation on Their Adoption and Sustainability as a Purpose of Education

Abstract: The aim of this paper to develop a model to measure sustainability for education and incorporate the literature big data adoption and knowledge management sharing in the educational environment. This paper hypothesizes that perceived usefulness, perceived ease of use, perceived risk, and behavioral intention to use big data should influence adoption of big data, while age diversity, cultural diversity, and motivators should impact knowledge management sharing. Therefore, knowledge management sharing influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 81 publications
(111 reference statements)
7
64
0
1
Order By: Relevance
“…Through these characteristics, public sharing of information, engagement, and collaborative learning became famous features of these social networking sites [5,12,25,41,50]. This research supports the SMU to improve the students skills via their peer interactions [51,52]. Their satisfaction in SMU boosts their technology use, and in turn, this use enhances their skills and improves their achievement through collaboration and interaction [3,5,7,53,54].…”
Section: B Discussion and Implicationsmentioning
confidence: 74%
“…Through these characteristics, public sharing of information, engagement, and collaborative learning became famous features of these social networking sites [5,12,25,41,50]. This research supports the SMU to improve the students skills via their peer interactions [51,52]. Their satisfaction in SMU boosts their technology use, and in turn, this use enhances their skills and improves their achievement through collaboration and interaction [3,5,7,53,54].…”
Section: B Discussion and Implicationsmentioning
confidence: 74%
“…Therefore, students have to track and analyze the collaboration patterns that occur during ACL. ACL and motivating cognitive skills, reflection and metacognition, are fundamental to SMAs for learning [8]. The current research looks at the issues of education sustainability by using SMAs, thus, some studies have demonstrated that a higher level of learning was achieved as a result of using SMAs for student assignments [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proposed approach is a data analysis technique that should be useful to those who seek to use UGC to improve their communication or marketing strategies. Also, it should be useful to educational institutions that may be able to enhance their offerings by identifying needs and trends based on technologies previously investigated [52][53][54][55]. Figure 1 shows the training process of the SVM algorithm and the classification according to the feelings that (a) represents the training process of a sentiment analysis algorithm with a feature extractor and a machine learning algorithm, and (b) represents the prediction process of a sentiment analysis algorithm with a feature extractor and a classifier model [2].…”
Section: Knowledge-based Methods To Extract Insights From Ugcmentioning
confidence: 99%